Chapter 37 A Systematic Literature Review of Game-based Learning and Gamification Research in Asia The synthesized findings and research gap - So, Hyo- Jeong (Taylor & Francis, 2018)
The main purpose of this research is to conduct a systematic literature review of research studies on game-based learning and gamification conducted in Asian K-12 schools. Through this review, we intend to present a comprehensive analysis of what the body of accumulated research informs us of the impact of games in Asian educational settings and to draw implications for future research directions.